Towards sustainable cities: native plants on experimental rooftops promote higher insect abundance than exotics - Fenoglio, Maria Silvina (2020)
As urbanization continues growing, green roofs design emerges as a promising alternative to enhance plants and animals within cities. The scarce evidence available, nevertheless, gives no clear advantage of plants’ origin on insect abundance. By using an experimental approach where the origin of the plant species (native-exotic) was manipulated across an urbanization gradient, we evaluated their efficiency as surrogate habitats for insects in Cordoba city, central Argentina. To do so we installed, in each of 30 houses, two blocks of a modular extensive green roof system (3m2 each), with either native or exotic plant species (6 species each). In March 2019 we used pan yellow traps to sample insects, whereas the level of urbanization of each house was estimated by using NDVI and surface temperature in a buffer of 400m. A total of 9024 insects from 10 taxonomic orders were registered, being Diptera (40%), Hymenoptera (21%), Hemiptera (21%) and Thysanoptera (14%) the dominant groups. We found a significant effect (χ2 =11.58; p<0.0001) of the origin of plant species on total insect abundance, but non-effect of urbanization degree. Native plants sustained significantly more insects (median= 165,5; q1-q4=78.25-419) than exotics (median=115; q1-q4=78,25-312). This suggests that native plants on green roofs promote a higher abundance of insects than exotics probably due to the first share a greater evolutionary history with local fauna. On the way to achieve more sustainable, greener cities, our results highlight that the origin of vegetation should be taken into account in green roof design to better achieve urban insect conservation.